Perfil imunofenotípico de células linfóides circulantes em pacientes soropositivos para o vírus linfotrópico de células T humanas - I - Souza, Geane Félix de (2002)
HTLV-I and II viruses convert their genomic RNA to DNA employing the enzyme reverse transcriptase, a RNA-dependent DNA polymerase, which makes possible their integration into host cell genorne. Common ways of transmission are: sexual intercourse, transfusion of hemoderivative components and the shared use'of contaminated syringes and needles. The prevalence of the infection varies signifícantly with the geographic region, the racial group and the sub-population under risk. About 1 to 4% of the infected individuais develop some form of infection-related disease. The association of HTLV-I with Adult T - Cell Leukemia, as well as the Tropical Spastic Paraparesis, is presently well recognized. Although the majority of HTLV-I-infected individuais remain asymptomatic, there are indications that cellular responses are functionally impaired in these cases. As the immunophenotypic profíle of peripheral blood lymphoid cells reflect on the performance of the immune system, a study was carried out on the behavior of CD3+, CD4+, CD8+ T lymphocytes and the CD4+/ CD8+ ratios in 35 symptomatic or asymptomatic HTLV-I- infected individuais. The age distribution and the hematological parameters were investigated and compared to those of seronegative individuais. In the demographic analysis of the cases, a predominance of infection in females was observed with a higher average age in the group of seropositive symptomatic individuais.